2014
DOI: 10.1152/ajpgi.00203.2013
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor enhances cholinergic contraction of longitudinal muscle of rabbit intestine via activation of phospholipase C

Abstract: Al-Qudah M, Anderson CD, Mahavadi S, Bradley ZL, Akbarali HI, Murthy KS, Grider JR. Brain-derived neurotrophic factor enhances cholinergic contraction of longitudinal muscle of rabbit intestine via activation of phospholipase C. Am J Physiol Gastrointest Liver Physiol 306: G328 -G337, 2014. First published December 19, 2013 doi:10.1152/ajpgi.00203.2013.-Brain-derived neurotrophic factor (BDNF) belongs to the neurotrophin family of proteins best known for its role in neuronal survival, differentiation, migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 58 publications
5
51
1
Order By: Relevance
“…Preliminary studies (data not shown) indicated that BDNF synthesis and secretion are not affected by acetylcholine. This is consistent with the lack of effect of Trk B antagonists and antiserum alone on the BDNF‐induced augmentation of cholinergic contractions . Substance P increased the expression of BDNF to approximately the same degree as did PACAP.…”
Section: Discussionsupporting
confidence: 82%
“…Preliminary studies (data not shown) indicated that BDNF synthesis and secretion are not affected by acetylcholine. This is consistent with the lack of effect of Trk B antagonists and antiserum alone on the BDNF‐induced augmentation of cholinergic contractions . Substance P increased the expression of BDNF to approximately the same degree as did PACAP.…”
Section: Discussionsupporting
confidence: 82%
“…This compound selectively binds and activates the BDNF receptor, TrkB, and initiates its intracellular signaling pathways in vitro and in vivo (40, 6668). Previous studies showed that LM22A-4 activates ERK signaling via TrkB (67, 69, 70) and that BDNF reduced alcohol drinking via the activation of ERK signaling (19).…”
Section: Discussionmentioning
confidence: 99%
“…Bladder compliance was determined using the formula, (V N − V M )/(P N − P M ), where V represents bladder capacity, P represents bladder pressure, M represents initiation of bladder filling and N represents initiation of voiding. 20 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, bladder wall thickening causes poor detrusor smooth muscle compliance and affects smooth muscle contractility. 20 Thus, the role of NMDAR in regulating bladder function during cystitis was also investigated.…”
mentioning
confidence: 99%